Heterotopic Ossification in a Patient With Hemiplegia: A Case Report and a Brief Rewiev of the Literature - Süleyman Tatlı; Ayhan Kamanlı; Salih Özgöçmen; Özgeç Ardıçoğlu (Galenos Yayinevi, 2002)
Heterotopic ossification (HO) is a biological process characterized by the formation of genuine new bone in tissues that do not ossify under normal conditions. Herein a 75-year-old woman who developed HO in her left hemiplegic hip following a hemorrhagic stroke is presented.